The ethnolinguistic situation of the Aromanians(Vlachs) in Macedonia - Šatava, Leoš (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2013)
The text presents the outcome of a sociolinguistic questionnaire survey conducted among the pupils attending lessons in the Aromanian (Vlach) language at a primary school in Kruševo (Macedonia). The survey focused on: the rate of use of Aromanian in individual language domains; the proportion of Aromanian in the overall framework of speaking activities; the reception of Aromanian culture and active participation in this culture; and subjective ethnic, linguistic and cultural attitudes and assessments. With respect to the current situation of the Aromanian language, the questionnare detected decisive differences among individual respondents concerning the mother tongues of the parents, gender and other aspects. Computing the (non)homogeneity of the answers proved highly relevant as well.
Keywords: Aromuni; Vlachs; Vlahi; Makedonija; Republic of Macedonia; Kruševo; jezikovne manjšine; mladina; etnolingvistični položaj; sociolinguistics; sociolingvistika